A Numerical Model to Study the Nonlinear and Unsteady Aerodynamics of Bioinspired Morphing-Wing Concepts. Issue 3 (September 2015) - Verstraete, Marcos L.; Preidikman, Sergio; Roccia, Bruno A.; Mook, Dean T.
In the present paper, a numerical model to study the nonlinear and unsteady aerodynamics of morphing-wing concepts inspired by bird flight is developed. The model includes: i ) a wing topology inspired by gull wings; ii ) a kinematical model to describe the process of wing adaptation based on one mechanism observed in the flight of gulls (folding-wing approach); and iii ) a version of the unsteady vortex-lattice methods (UVLM) that allows taking nonlinear and unsteady aerodynamic phenomena into account. The model was specially developed to study the aerodynamic behavior during wing adaptation. A simulation for a twisting-flapping wing was performed in order to validate the numerical model. The present results are in close agreement with those obtained in previous studies based on the Euler equations, but required much less execution time. The numerical simulations of a bioinspired morphing wing showed the strong dependence between the prescribed kinematics and the aerodynamic characteristics, which evidences the importance of studying the process of wing adaptation. UVLM is shown to be ideal for preliminary analysis of bioinspired morphing wings.